2017
DOI: 10.1038/s41598-017-02764-3
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient and herbivore alterations cause uncoupled changes in producer diversity, biomass and ecosystem function, but not in overall multifunctionality

Abstract: Altered nutrient cycles and consumer populations are among the top anthropogenic influences on ecosystems. However, studies on the simultaneous impacts of human-driven environmental alterations on ecosystem functions, and the overall change in system multifunctionality are scarce. We used estuarine tidal flats to study the effects of changes in herbivore density and nutrient availability on benthic microalgae (diversity, abundance and biomass) and ecosystem functions (N2-fixation, denitrification, extracellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 63 publications
(93 reference statements)
0
6
0
Order By: Relevance
“…Species richness tends to decrease less with grazing (Liess and Hillebrand , Alberti et al. ) because tolerant understory species are grazer resistant, while sensitive overstory species can still be present, even if they cannot accumulate considerable biomass, e.g., by maintaining basal growth (Lamberti et al. , Steinman ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Species richness tends to decrease less with grazing (Liess and Hillebrand , Alberti et al. ) because tolerant understory species are grazer resistant, while sensitive overstory species can still be present, even if they cannot accumulate considerable biomass, e.g., by maintaining basal growth (Lamberti et al. , Steinman ).…”
Section: Introductionmentioning
confidence: 99%
“…, Alberti et al. ), shown to cause a logarithmic decline in algal standing crop (Lamberti et al. ) and prevent nuisance levels of filamentous algae (high profile guild) under eutrophication (Anderson et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This follows because changes in community composition may alter trait‐based community properties (Cardinale et al., 2012), with consequences for ecosystem functions, even in the absence of changes in summary measures (diversity, cover; Lefcheck & Duffy, 2015; O’Connor & Donohue, 2013). For example, studies have shown that nutrient enrichment can alter ecosystem functions such as productivity or nitrogen fixation through altered relative species abundances at rates disproportional to those of changes in diversity (tidal flats, no effects on diversity: Alberti et al., 2017; grasslands: Isbell et al., 2013). Our results highlight the need to incorporate temporal turnover in investigations of anthropogenic impacts on assemblage structure and function; they suggest that systems strongly driven by either top–down or bottom–up forces may experience a decoupling of diversity and ecosystem function measures with anthropogenic stress (Souza et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Increasingly, studies have examined the relative roles of these two factors on plant biomass or diversity (e.g. Alberti et al., 2017; Hillebrand et al., 2007; Souza, Zelikova, & Sanders, 2016). Yet diversity, a measure of the number and relative abundance of species within a defined scale or study unit (Magurran, 2004; Schleuter, Daufresne, Massol, & Argillier, 2010), is underpinned by a complex array of temporally variable processes that define the structure and dynamics of the community (Magurran & Henderson, 2010).…”
Section: Introductionmentioning
confidence: 99%